DETECTION EARLY BREAST CANCER BY USING DIGITAL INFRARED IMAGE BASED ON ASYMMETRY THERMAL - Dringhuzen Jekke Mamahit (Universitas Sam Ratulangi, 2012)
Breast cancer is a health risk main to woman. Thegrowth hardly quickly and can result death for patient.Principal worked Digital infra-red mall imagery applied fordiagnosa non invasive which enable praktisis klinis dovisualisation and quantification of change of mall surface ofhusk.One of the methods for breast cancer detection is tomake comparisons between contralateral images. When theimages are relatively symmetrical, small asymmetries mayindicate a suspicious region. In thermal infrared (IR) imaging,asymmetry analysis normally needs human intervention becauseof the diculties in segmentation image processing. In ordertoprovide a more objective diagnostic result, we describe anautomatic approach to asymmetry analysis in thermograms. Itincludes automatic segmentation and supervised patternclassication.